Scientific Literacy and Environmental Awareness through Undergraduate Student Worksheets Based on Socioscientific Issues - Hanifha, S.; Erna, M.; Noer, A. M.; Talib, C. A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Scientific literacy and environmental awareness are skills needed in the 21st century. Therefore, education must provide these skills. This research aims to analyze the effect of SSI-based undergraduate student worksheets on chemical thermodynamics. Pre-experimental research with a pretest-posttest control group design was employed to compare SSI-based and science-based undergraduate student worksheets. Chemistry education students at FKIP Universitas Riau for the 2022/2023 academic year were selected as samples. The experimental and control groups were established based on the homogeneity of their previous academic scores. This study evaluated two outcome variables: scientific literacy ability and environmental awareness. The research instrument is a scientific literacy test using scientific literacy description questions and environmental awareness questionnaires. Scientific literacy test scores were analyzed using the Independent Sample T-test, and environmental awareness questionnaire results were analyzed using the Mann-Whitney U-Test. Increased scientific literacy and environmental awareness of students were analyzed using the N-gain test. The results showed that the experimental group's scientific literacy and environmental awareness were significantly higher than the control group. Therefore, it can be concluded that SSI-based undergraduate student worksheets effectively increase scientific literacy and environmental awareness.